SOSIALISASI AUTIS DI YAYASAN ALFATH SIAK KECAMATAN SIAK KABUPATEN SIAK - Monalisa Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Autism is complex developmental disorder, associated with communication, social interaction and behavior. Children with autism in the development process requires special handling that is different from normal children in general. Therapy is a form of alternative in treating autism assisted by a special education program . it is intended to provide assistance as needed in order to run a good socialization process so that children can live independently.This research uses qualitative methods. Data collection techniques used in this study were interviews and observation. The number of subject in this study were 10 respondents who include teachers or therapists 7 in the foundation of Alfath and 3 parents who have children with autism who undergo therapy and education process in the foundation of Alfath.The result of this study indicate that teachers are therapists and families play an important role in the socialization of children with autism early. Socialization by Alfath Siak foundation through therapy program for children with autism in accordance with the needs and provide special aducation for children with autism choose a different socilazation patterns. The dominant patterns. The dominant patterns of socialization is done in the foundation Alfath Siak is participatory socialization patterns, this is due to the participation of children with autism is the most important thing of the socialization process. Participatory socialization patterns also emphasizes the interactions the interaction of the child as the center of socialization. To support an increase in the socialization of children with autism, the role of teacher or therapist and the family becomes very important agent of socialization. The teacher‟s role in the socialization of children with autism not only do in foundation, but teachers also play a home for children with autism. So that the need for better cooperation between teachers and parents in dealing autismchildren.Keyword : Autism, Therapy and Socialization